2008
DOI: 10.1016/j.ejcts.2008.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication and prognostic significance of standardised uptake value of primary non-small cell lung cancer on positron emission tomography: analysis of 176 cases☆

Abstract: SUV(max) correlates with tumour characteristics, surgical stage and prognosis following resection. SUV(max) may be a useful preoperative tool, in addition to other known prognostic markers, in allocating patients with potentially poor prognosis preoperatively to neoadjuvant chemotherapy prior to resection in order to improve their overall survival. Prospective and randomised trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 18 publications
9
68
1
3
Order By: Relevance
“…The lower SUVmax of adenocarcinomas is consistent with the results of other studies [1,2]. Tumour subtype is known to reflect the differential avidity of 18FDG uptake by cancer cells [21]. Glucose transporters mediate FDG uptake, and the expression of these proteins has been found to correlate with FDG uptake [22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The lower SUVmax of adenocarcinomas is consistent with the results of other studies [1,2]. Tumour subtype is known to reflect the differential avidity of 18FDG uptake by cancer cells [21]. Glucose transporters mediate FDG uptake, and the expression of these proteins has been found to correlate with FDG uptake [22].…”
Section: Discussionsupporting
confidence: 86%
“…Adenocarcinomas were reported to express low levels of Glut-1 [24]. These tumours have a lower 18FDG uptake and a lower SUVmax than squamous cell tumours [21]. However, although Glut-1 is the major glucose transporter expressed in NSCLC, it is neither the sole nor the rate-limiting determinant of FDG uptake [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a SUV max cutoff value of 7.5 was selected using the lowest log-rank test P value (supplemental online Figure 2), which was the same procedure reported by other studies [11,14]. When we further analyzed this SUV max cutoff in each primary tumor subtype, this value of 7.5 was also defined in GB Ca and AoV Ca but not ICC (supplemental online Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that differences in cutoff values of PET SUV max are attributable to different cancer subtypes [11]. Others claim that more analyses with larger numbers of cases or independent studies are needed to determine the most appropriate cutoff point and thereby decrease the risk of falsepositive results [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation